Endovascular stenting for the management of port-a-cath associated superior vena cava syndrome - Kostopoulou, V.; Tsiatas, M. L.; Kelekis, D.A.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Emergency Radiology, 2009)
Port-a-cath systems are often essential for the administration of long-term chemotherapy in the treatment of malignancies because they improve venous access, but they are associated with complications, mainly thrombosis of central veins. In the present report, we describe a case of right subclavian and superior vena cava port-a-cath-related thrombosis causing superior vena cava syndrome (SVCS) in a patient affected by Hodgkin's disease. The patient underwent percutaneous revascularization with stent positioning, experiencing immediate relief of symptoms. Endovascular procedures for the treatment of nonmalignant SVCS seem to represent a challenging therapeutic option. © 2008 Am Soc Emergency Radiol.
Keywords: Port-a-cath; Stent; Superior vena cava syndrome; Thrombosis